Differential Effects of Eicosapentaenoic Acid and Docosahexaenoic Acid on Serum Metabolome - Chang, Wan Chi; So, Jisun; Lamon-Fava, Stefania (Current developments in nutrition, 2021)
The omega-3 fatty acids eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) have been shown to have shared and independent effects on inflammation and on lipid and glucose metabolism. However, the differential effects of EPA and DHA on serum metabolome remain elusive in humans. Twenty-one subjects (9 men and 12 women, 50–75 y) with chronic inflammation (C reactive protein > 2 μg/mL) were enrolled in a randomized, controlled crossover trial consisting of a 4-week lead-in phase (high oleic sunflower oil, 3 g/d; baseline) followed by randomization to two sequential 10-week supplementation phases with pure EPA and DHA (3 g/d each) separated by a 10-week washout. Primary metabolites (n = 129) were measured in fasting serum samples by gas chromatography-mass spectrometry. Linear-mixed model was created to compare changes in metabolites by EPA and DHA relative to baseline. Pathway analysis (MetaboAnalyst 4.0, https://www.metaboanalyst.ca) was performed to identify the biological pathways associated with affected metabolites. DHA altered a greater number of metabolites than EPA (19 vs 11). Both EPA and DHA significantly lowered constitutive metabolites of the TCA cycle and the alanine, aspartate and glutamate metabolism pathway, with DHA showing a greater reduction than EPA. EPA significantly increased UDP-glucuronic acid and glucuronic acid, and DHA increased only glucuronic acid, thus affecting pathways where these metabolites play key roles (ascorbate and aldarate metabolism; pentose and glucuronate interconversions). DHA affected more metabolites than EPA. The greater impact of DHA on the TCA cycle and the larger effect of EPA on the glucose-derived glucuronic acid-related pathways suggest their differential ability to modulate metabolic pathways. Grant number: 2015–67,017-23,142 from the National Institute of Food and Agriculture, U.S. Department Of Agriculture.